1999
DOI: 10.1046/j.1432-1327.1999.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of species‐specific O‐linked carbohydrate chains from oviducal mucins inRana arvalis

Abstract: The extracellular matrix surrounding amphibian eggs is composed of mucin-type glycoproteins, highly O-glycosylated and plays an important role in the fertilization process. Oligosaccharide-alditols were released from the oviducal mucins of the anuran Rana arvalis by alkali-borohydride treatment in reduced conditions. Neutral and acidic oligosaccharides were fractionated by ion-exchange chromatographies and purified by HPLC. Each compound was identified by matrix assisted laser desorption ionization-time of fli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 29 publications
3
26
2
Order By: Relevance
“…With regard to amphibians, a study on the salamander Ambystoma macrodactylum indicated that sialic acid may play a role in jelly water retention (Berner and Ingermann 1990). However, mass spectrometric studies found no evidence of sialic acid in jelly of R. arvalis (Coppin et al 1999), which we confirmed for our study populations using a sialic acid detection kit (data not shown). Thus, other mechanisms are needed for variation in R. arvalis water balance in relation to pH.…”
Section: General "Ph-jelly Water Balance" Modelsupporting
confidence: 76%
See 1 more Smart Citation
“…With regard to amphibians, a study on the salamander Ambystoma macrodactylum indicated that sialic acid may play a role in jelly water retention (Berner and Ingermann 1990). However, mass spectrometric studies found no evidence of sialic acid in jelly of R. arvalis (Coppin et al 1999), which we confirmed for our study populations using a sialic acid detection kit (data not shown). Thus, other mechanisms are needed for variation in R. arvalis water balance in relation to pH.…”
Section: General "Ph-jelly Water Balance" Modelsupporting
confidence: 76%
“…However, although glycans are often a key component of egg coats, and egg coats have fundamental biological functions from fertilization to protection from environmental hazards (Menkhorst and Selwood 2008;Shu 2014), to date next to nothing is known about intra-specific glycan variation of egg coats, or the functional and evolutionary consequences of this diversity. Most studies to date have focused on quantifying glycan compositional variation among taxa (e.g., Coppin et al 1999). In a rare study, intra-specific polymorphism, equivalent of human blood groups, was found in the macromolecular composition of the egg jelly in X. laevis-but the functional consequences remained unclear (Guerardel et al 2000).…”
Section: Role Of Extracellular Glycan Diversity In Adaptive Evolutionmentioning
confidence: 99%
“…The SO 3 Ϫ 33Gal structure in O-linked and N-linked glycans has been found in various glycoproteins including thyroglobulin (4 -6), meconium glycoproteins (7), respiratory mucous glycoproteins from patients with cystic fibrosis (8 -10) and chronic bronchitis (11), an ovarian cystadenoma glycoprotein (12), LS174T-HM7 colon carcinoma mucin (13), Tamm-Horsfall glycoprotein (14), sulfomucins (15), and oviducal mucins (16). Sulfated residues in these glycoproteins are attached to C-3Ј of Gal␤133/4GlcNAc, Gal␤133GalNAc, or Gal␤133Gal structure.…”
mentioning
confidence: 99%
“…This result indicates that the 6-O-sulfated N-acetyllactosamine structure occurs extensively. In fact, this sulfated glycan moiety has been shown to be present in various glycoproteins including ovomucin (65), glycoproteins derived from several culture cells (66), thyroglobulin (67), zona pellucida glycoproteins (68,69), gp120 of human immunodeficiency virus type 1 (70), respiratory mucins (71,72), carcinoembryonic antigen (73), hyosophorin (74), and oviducal mucins (75). 6SGN-specific ␤4GalT-IV identified in this study may be useful to elucidate the biological roles of these sulfated moieties.…”
Section: ␤4galt-iv Is Specific For Glcnac 6-o-sulfatementioning
confidence: 99%